Strategi Kolaboratif Pengembangan Ekowisata Berkelanjutan Melalui Peningkatan Kapasitas Sumber Daya Manusia di Kalurahan Bimomartani: Pengabdian - Joko Sutopo; Sunardi; Mustaqim Pabbajah; Juhansar; Fiya Ainur Rohmatika; Novi Faulia Sari; Dedek Darvina; Angga Muhammad Zacky; Iskandar Zulkarnain; Rico Fitra Pratama; Rizqulloh Brilliant 'Ainur Rofiq (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Ecotourism-based village tourism is a sustainable development strategy that balances economic, social, and ecological aspects. Bimomartani Village, Sleman, has the potential for reservoirs, agriculture, rural landscapes, and local culture, but is hampered by limited human resource capacity and digital promotion. This community service activity aims to formulate a collaborative strategy for ecotourism development through human resource development and digital promotion using the Participatory Action Research (PAR) method, which involves the community in planning and reflection. Results show that training in hospitality, homestay management, tourism narratives, and digital marketing increased community engagement. The pentahelix collaborative model also strengthens the synergy between government, academics, communities, the private sector, and the media. In conclusion, a collaborative strategy based on human resources and digitalization can realize inclusive, technology-adaptive, and sustainable community ecotourism in Bimomartani Village.